Analysis of the Effect of Temperature Variations on HC-SR04 Ultrasonic Sensor Distance Measurement Accuracy Based on Tinkercad Simulation - Rismawaty Arunglabi; Nicolaus Allu; Hendrick Jackson Andreas Patandianan (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2026)
Ultrasonic sensors are used to measure distance based on the reflection of sound waves. However, their accuracy is influenced by temperature changes because temperature determines the speed of sound propagation in air. This study analyzes the effect of temperature variations on the performance of ultrasonic sensors through theoretical analysis and Tinkercad simulation within a range of 0°C to 50°C. The method includes calculating the speed of sound as a function of temperature, analyzing the wave travel time, and simulating distance measurements in a virtual environment. The error value is obtained by comparing the sensor readings with the actual distance. The results show that higher temperatures increase the speed of sound, causing the measured distance to appear shorter, while lower temperatures result in longer readings. The smallest error occurs at 19°C–20°C, when the speed of sound approaches 343 m/s. At extreme temperatures, the measurement error can exceed 5%. These findings confirm that temperature is a key factor affecting ultrasonic sensor accuracy and can serve as a reference for the development of automation and industrial monitoring systems